2012
DOI: 10.1016/j.otsr.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Bone transport techniques in posttraumatic bone defects

Abstract: Level IV. Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 11 publications
0
65
1
Order By: Relevance
“…2,3,32,33 However, it remains indisputable that the main disadvantage of the Ilizarov technique is the tedious process with external fixation that may take months to perform. Intense pin-track pain appeared in two patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,32,33 However, it remains indisputable that the main disadvantage of the Ilizarov technique is the tedious process with external fixation that may take months to perform. Intense pin-track pain appeared in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…Compound tibia fracture with significant zone of injury or sequelae of bone healing complications can be managed with complex methods including the Ilizarov technique of distraction osteogenesis, 1,2 the Masquelet technique, 3 or vascular bone transfers, such as the iliac crest and fibula. 4 In cases of extensive soft-tissue loss, local or pedicled muscle flaps or free flaps may be indicated.…”
Section: Introductionmentioning
confidence: 99%
“…ii) Good clinical efficacy of calcium sulfate as a bone substitute. In a previous study regarding the use of calcium sulfate as a bone graft substitute to repair bone defects ranging from 13-138 cm 3 , Kumar et al (15) concluded that calcium sulfate is a safe, efficient and easily available bone graft substitute for the treatment of osseous defects. Similarly, in a 3-year randomized controlled trial, Di Alberti et al (16) also reported good outcomes of calcium sulfate as a carrier for regeneration of human bone defects.…”
Section: Calcium Sulfate Can Induce the Formation Of Membranementioning
confidence: 99%
“…Autologous bone graft is not recommended for reconstruction of massive bone defects due to its increased risk of resorption (2). Vascularized fibular autograft and the Ilizarov bone transfer technique are the most frequently used methods for reconstruction of extensive bone defects (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of posttraumatic diaphyseal bone defects (BD) calls for a number of techniques including bone transport techniques , shortening, compression-distraction at the fracture site, shortening followed by lengthening in a corticotomy distant from the site and segmental bone transport [1]. the earliest treatment for these problems included amputation or shortening where as more recent treatments have included bone lengthening, bone grafting, titanium mesh cage packed with allograft and distraction osteogenesis [2].…”
mentioning
confidence: 99%